Investigating the Experience of a Female Seafarer through a Gender Photo Lens - Banun Havifah Cahyo Khosiyono; Ista Maharsi; Mia Fitria Agustina (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This article examines how a woman seafarer uses an image to create her identity and struggles in a male-dominated job. Photovoice and online interviews were used to gather data. While the purpose of the interview was to gather the narratives, the SHOWeD approach helped her think about the picture. Content analysis was used to examine the data to find themes and recount the tales of her identity creation. The results demonstrate that while regulations have been put in place to safeguard women working on ships and to ensure that male and female seafarers have equivalent workloads, there is no assurance that harassment and discrimination won't happen. The male counterpart's unfavorable stigmatization of women working on ships regrettably confirms that women seafarers continue to be a high-stakes profession with possible hazards. One important identity construction that emerges is that women seafarers do not pursue careers that last a lifetime because other jobs are seen as more fulfilling, such working in an office and raising children.